2001
DOI: 10.1121/1.1359797
|View full text |Cite
|
Sign up to set email alerts
|

The lower limit of melodic pitch

Abstract: An objective melody task was used to determine the lower limit of melodic pitch (LLMP) for harmonic complex tones. The LLMP was defined operationally as the repetition rate below which listeners could no longer recognize that one of the notes in a four-note, chromatic melody had changed by a semitone. In the first experiment, the stimuli were broadband tones with all their components in cosine phase, and the LLMP was found to be around 30 Hz. In the second experiment, the tones were filtered into bands about 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(130 citation statements)
references
References 45 publications
9
118
2
Order By: Relevance
“…Frequency discrimination threshold, expressed as the just noticeable pitch interval in cents, markedly increases with decreasing tone frequency below 200 Hz (Wier et al, 1977;Rakowski, Miśkiewicz, 2002) which means that a tone's pitch becomes less salient and less pronounced than the pitch of higher-frequency tones. Similar findings of a weaker pitch of the low frequency tones were also observed in a study of the pitch strength of musical instrument tones conducted with the use of absolute magnitude estimation method (Rogala, 2008) as well as in the studies in which musically trained listeners identified the notes of a melody made up of synthetic complex tones (Pressnitzer et al, 2001) or musical instrument sound samples (Rogala, 2010).…”
Section: Introductionsupporting
confidence: 55%
“…Frequency discrimination threshold, expressed as the just noticeable pitch interval in cents, markedly increases with decreasing tone frequency below 200 Hz (Wier et al, 1977;Rakowski, Miśkiewicz, 2002) which means that a tone's pitch becomes less salient and less pronounced than the pitch of higher-frequency tones. Similar findings of a weaker pitch of the low frequency tones were also observed in a study of the pitch strength of musical instrument tones conducted with the use of absolute magnitude estimation method (Rogala, 2008) as well as in the studies in which musically trained listeners identified the notes of a melody made up of synthetic complex tones (Pressnitzer et al, 2001) or musical instrument sound samples (Rogala, 2010).…”
Section: Introductionsupporting
confidence: 55%
“…The value of tau (ms) was varied per CF based on Cariani (2004; tau=30 ms for CFG100 Hz; tau=16 ms for 100≤CFG440 Hz; tau=12 ms for 440 ≤ CF G880 Hz; tau = 10 ms for 880 ≤ CF G 1320 Hz; tau=9 ms for CF≥1320 Hz). The CFdependent time constants of the exponential functions were designed to account for the lower F0 limit (i.e.,~30 Hz; Pressnitzer et al 2001) and the effect of peripheral filtering on pitch perception (Bernstein and Oxenham 2005). The pooled ACF was then computed by summing across these multiplied ACFs to obtain periodicity information across 100 fibers.…”
Section: Motivation and Rationale For The Modeling Approachmentioning
confidence: 99%
“…In awake marmoset AI, neural responses to stimulus repetition rates below ~40 Hz (near the lower limit of pitch [61,62]) are represented temporally by stimulus-synchronized discharges, while a monotonically tuned rate code is used by another population of neurons to represent higher repetition rates [58]. Neurons with harmonically related multi-peaked frequency response areas have previously been observed in marmoset AI [59], although they differ from pitch-selective neurons in that their primary frequency tuning and harmonic responses are most commonly outside the frequency range of pitch perception, and that they respond to each component of a complex harmonic tone.…”
Section: Evidence From Non-human Primate Studiesmentioning
confidence: 99%